2014
DOI: 10.1186/1471-2164-15-s12-s5
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive data mining comparison of the effects of low doses of ionizing radiation, formaldehyde and dioxins

Abstract: BackgroundIonizing radiation in low doses is the ubiquitous environmental factor with harmful stochastic effects. Formaldehyde is one of the most reactive household and industrial pollutants. Dioxins are persistent organic pollutants and most potent synthetic poisons effective even at trace concentrations. Environmental pollutants are capable of altering the expression of a variety of genes. To identify the similarities and differences in the effects of low-dose ionizing radiation, formaldehyde and dioxin on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…After 9 h of malathion exposure, no mortality was observed in SE-Sto and RAL-375, while 15% and 25% mortality was observed in RAL-177 and iso-1, respectively. Overall, the number of DEGs ranged from 153 to 2778, similar to other transcriptomic studies performed with xenobiotics (figure 1 and table 1; electronic supplementary material, table S1B-E) [58,82]. Among these DEGs, we found several xenobiotic-related genes including Cyp12d1-d, Cyp6g1, Jheh1 and Jheh2, that have previously been identified as major malathion resistance loci (electronic supplementary material, table S1F) [83].…”
Section: Resultssupporting
confidence: 80%
“…After 9 h of malathion exposure, no mortality was observed in SE-Sto and RAL-375, while 15% and 25% mortality was observed in RAL-177 and iso-1, respectively. Overall, the number of DEGs ranged from 153 to 2778, similar to other transcriptomic studies performed with xenobiotics (figure 1 and table 1; electronic supplementary material, table S1B-E) [58,82]. Among these DEGs, we found several xenobiotic-related genes including Cyp12d1-d, Cyp6g1, Jheh1 and Jheh2, that have previously been identified as major malathion resistance loci (electronic supplementary material, table S1F) [83].…”
Section: Resultssupporting
confidence: 80%
“…Recent transcriptome studies showed that a broad range of stress treatments (e.g. cold, heat, caffeine, paraquat, rotenone, copper, zinc, cadmium, formaldehyde, dioxin, and low doses of ionizing radiation) differentially affects expression of both general and specific stress response genes [ 9 - 11 ]. General stress responses in Drosophila melanogaster include the activation of genes of cell cycle control, formation of gametes, circadian rhythms, splicing, proteolysis, and various aspects of metabolism [ 10 ], as well as genes that encode lysozymes, cytochrome P450s, and mitochondrial components mt:ATPase6, mt:CoI, mt:CoIII [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant change in the studied lifespan parameters was found only at an age of 10% and 15% mortality by 4−11% for both magnetites (Table 3, p < 0.05), whereas the females were powerfully affected, probably due to physiological differences in the sexes. In the article of Moskalev in 2014 35 it was shown that exposure to ionizing radiation and ecotoxicants has a lesser effect on gene expression than the gender factor.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%